2020
DOI: 10.1101/2020.09.09.290130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new mechanism of fibronectin fibril assembly revealed by live imaging and super-resolution microscopy

Abstract: Fibronectin (Fn1) is an essential ECM glycoprotein important for embryonic development and homeostasis. The functions of Fn1 in regulating cell fate decisions, morphogenesis and cellular responses to injury are intimately linked to the process of Fn1 fibrillogenesis. Therefore, understanding the mechanisms by which Fn1 proteins assemble into fibrils is necessary to gain insights into diverse functions of Fn1. Using CRISPR/Cas9 mutagenesis, we generated mice and cell lines wherein a sequence encoding a fluoresc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 106 publications
(231 reference statements)
1
3
0
Order By: Relevance
“…Our previous finding that members of the Lysyl oxidase enzyme family bind FN, that LOX-Like 3 (LOXL3) oxidizes it, and that its enzymatic activity induces FN-dependent integrin activation 23 , raised the possibility of an enzyme-dependent initiation of fibrillogenesis , a force-independent mechanism which relies on enzymes and their substrates’ availability. In line with this notion, we found that in cultured cells expressing GFP-tagged FN 24 , FN fibrils are observed under β1-integrin adhesions and LoxL3 is distributed at nascent adhesion sites (Figure 1A). Notably, LoxL3 is expressed in neural crest cells (Figure S1A) and following its deletion ( LoxL3 Δ/Δ ) the mutant embryos display a cleft palate phenotype and reduced neural crest cell numbers at branchial arches (Figure S1B-H), both of which are FN-associated phenotypes 25,26 .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Our previous finding that members of the Lysyl oxidase enzyme family bind FN, that LOX-Like 3 (LOXL3) oxidizes it, and that its enzymatic activity induces FN-dependent integrin activation 23 , raised the possibility of an enzyme-dependent initiation of fibrillogenesis , a force-independent mechanism which relies on enzymes and their substrates’ availability. In line with this notion, we found that in cultured cells expressing GFP-tagged FN 24 , FN fibrils are observed under β1-integrin adhesions and LoxL3 is distributed at nascent adhesion sites (Figure 1A). Notably, LoxL3 is expressed in neural crest cells (Figure S1A) and following its deletion ( LoxL3 Δ/Δ ) the mutant embryos display a cleft palate phenotype and reduced neural crest cell numbers at branchial arches (Figure S1B-H), both of which are FN-associated phenotypes 25,26 .…”
Section: Resultssupporting
confidence: 78%
“…To explore whether these mutations affect also FN fibrillogenesis, we first tested whether cells fibrilize their own secreted FN. To that end, we coated coverslips with Alexa 647-labelled FN and cultured MEF FN-GFP (in which GFP is knocked-in to both alleles of the FN gene 24 ) for 48 hours, followed by imaging of the FN fibrils. All FN fibrils we observed were GFP labelled, demonstrating that cells use their own secreted FN in forming the initial fibrils (Figure S3B-C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With improved resolution of microscopic techniques, we will also be able to obtain more detailed information. Use of super-resolution microscopy has recently shown that the FN fibrils are not continuous but consist of nanodomains [ 156 ]. As we learn more, it is likely that the unexpected will continue to surprise us.…”
Section: Who Is Leading the Way—fibronectin Or Collagen—or A Jointmentioning
confidence: 99%